Exploring Metaphysics of Unconscious (Ālaya- vijñāna): Thinking through Vasubandhu - Srivastava, Pankaj (Universal Research Reports, 2018)
Unconscious refers to a hidden side of one’s personality to which an individual is unaware but it influences all his/her thoughts, feelings and actions. In the west, Freud was the pioneer who discerned the unconscious aspect of human personality and developed a systematic theory of the unconscious mind. In India, seekers (rishis & yogis) through their meditative practices visualised various factors (unconscious) which play a significant role in the making of one’s psyche (chittā) Notably, Vasubandhu is considered to be one of the most prominent and influential thinkers who developed metaphysics of unconscious known as ālaya-vijñāna. This study explores the nature of the unconscious (ālaya-vijñāna) and its relationship with consciousness reading through Vasubandhu’ treatise popularly known as Vijñāptimatratasiddhi. This research paper has three main objectives: first, to understand the metaphysical framework of Vasubandhu concerning nature of consciousness. Second to explore the structure of unconscious (ālaya-vijñāna): how unconscious becomes the seat of all mental dispositions, tendencies, desire (vāsanā) clinging and grasping (upādān). How does it influence different aspects of personality such as cognitive, affective and connotative? Third, to analyse reciprocal causality between unconscious and consciousness against the backdrop of Buddhist’ idea of dependent origination.